Pengaruh Ekstrak Kulit Buah Naga Merah (Hylocereus Polyrhizus) terhadap Waktu Perdarahan (Bleeding Time) Pada Mencit Strain Balb-C - Dwi Mukti Kusumastuti; Zainul Cholid; Winny Adriatmoko (Fakultas Kedokteran Gigi Universitas Jember, 2021)
Tooth extraction causes prolonged bleeding complications and the body will respond with hemostasis. Currently developing natural medicines to help the process of hemostasis. Red dragon fruit peel, which is generally a waste containing tannins, flavonoids, and saponins to stop bleeding. Purpose was to find out the effect of red dragon fruit peel extract on bleeding time in the tail of Balb-C strain mice. 16 mice samples were adapted for one week. Mice were divided into 2 groups subsquently fasted for 7 hours. The first group as a control (0.5% Na-CMC). The second group was given red dragon fruit peel extract which was divided into three sub-groups at a dose of 0.5 mg / g BW, mg / g BW, and 1.5 mg / g BW. All samples were waited for 45 minutes and cut along 2 cm from the tip of the tail. Blood is spilled on Whatman paper which has 30 seconds in each box. The number of blood spots on the box was calculated and multiplied by 30 seconds. The result showed that bleeding time in the group given red dragon fruit peel extract was significantly lower (p <0.05) than in the control group. The conclusion was red dragon fruit peel extract (Hylocereus Polyrhizus) has an effect on shortening the bleeding time in cutting the tail of bulb-c strain mice and the dose of red dragon fruit peel extract (Hylocereus Polyrhizus) which has the most significant effect is 1 mg / BB mice.